2018
DOI: 10.1111/biom.12996
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Randomized Procedure for Large-Scale Heterogeneous Multiple Discrete Testing Based on Randomized Tests

Abstract: In the analysis of next‐generation sequencing technology, massive discrete data are generated from short read counts with varying biological coverage. Conducting conditional hypothesis testing such as Fisher's Exact Test at every genomic region of interest thus leads to a heterogeneous multiple discrete testing problem. However, most existing multiple testing procedures for controlling the false discovery rate (FDR) assume that test statistics are continuous and become conservative for discrete tests. To overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The authors showed that a simple randomization technique, which is not only limited to sequencing data but can be used for general discrete test statistics, can address this issue. In the case of multiple testing of heterogeneous discrete data, Dai et al (2019) proposed a procedure based on the marginal critical function (MCF) of randomized tests. The MCF approach provides a nonrandom decision that is based on ranked MCF values, although it utilizes randomized tests.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that a simple randomization technique, which is not only limited to sequencing data but can be used for general discrete test statistics, can address this issue. In the case of multiple testing of heterogeneous discrete data, Dai et al (2019) proposed a procedure based on the marginal critical function (MCF) of randomized tests. The MCF approach provides a nonrandom decision that is based on ranked MCF values, although it utilizes randomized tests.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of multiple testing of heterogeneous discrete data, Dai et al. (2019) proposed a procedure based on the marginal critical function (MCF) of randomized tests. The MCF approach provides a nonrandom decision that is based on ranked MCF values, although it utilizes randomized tests.…”
Section: Introductionmentioning
confidence: 99%